A new aphid species from Quercus frainetto in Italy, Tuberculatus (Tuberculoides) etruscus sp. n. (Homoptera Aphididae) (Bollettino di zoologia agraria e bachicoltura, 2024)
A new aphid species, Tuberculatus (Tuberculoides) etruscus sp.n., is described. Notes are given on morphology of viviparous morphs, distribution and ecology of the new taxon. Host plant is Quercus frainetto Ten. Taxonomical notes include a key to the alate viviparae of five species in the subgenus Tuberculoides v.d.G.
Keywords: Homoptera Aphididae; Tuberculatus (Tuberculoides) etruscus sp. n.; Quercusfrainetto; Italy